Stabilization of a ROV in Three-dimensional Space Using an Underwater Acoustic Positioning System. Issue 17 (2019) - Pedersen, Simon; Liniger, Jesper; Sørensen, Fredrik F.; Schmidt, Kenneth; Benzon, Malte von; Klemmensen, Sigurd S.
Abstract: In subsea applications there are an increasing demand for Remotely Operated Vehicles (ROV's). This study examines a BlueROV2 inspection ROV prototype for autonomous operation in three-dimensional space. This study describes the ROV modelling, identification, control development and closed-loop simulations and experiments. The main transmitter applied for the navigation is an Underwater Acoustic Positioning System (UAPS) which acts as an underwater GPS unit. The transmitter introduces a dominant output time delay which is handled by a smith predictor. The results show that the smith predictor does not handle the time delay well, probably because the time delay is time-variant. Online identification of the time delay is proposed as a potential solution for minimizing the impact of the time delay variations over time.